Geomorphology of the Caracota Valley, Western Altiplano, Northern Chile - Jan-Christoph Otto; Matias Gallardo; Luca Sitzia; Daniela Osorio; Eugenia M. Gayo (Journal of Maps)
We present a detailed geomorphological characterisation of the Caracota Valley (18°49′S 69°11′W, 4200–4600 m) in the western Altiplano of Northern Chile. A complex pattern of Pleistocene and Early Holocene glacier activity is responsible for the today's landscape configuration. Wetlands and temporary lakes significantly characterise the Caracota Valley setting providing water sources and storage required for life in this semi-arid landscape. Non-glacial processes at low intensities through most of the Holocene evoked little changes to the glacial landscape configuration, even though alluvial, fluvial and aeolian processes locally caused some sediment redistribution. The geomorphological study is embedded into a geoarchaeological research project on early human occupation in the zone of the Salar de Surire, Northern Chile, at 18°50′S. The geomorphological map offers a base to frame future discussions on the links between cultural and geomorphological places formation, which is a necessary step to move beyond site scales and ethnographic assumptions in the region of interest.